Adaptation of cell spreading to varying fibronectin densities and topographies is facilitated by β1 integrins - Lemma, Enrico Domenico; Jiang, Zhongxiang; Klein, Franziska; Landmann, Tanja; Weißenbruch, Kai; Bertels, Sarah; Hippler, Marc; Wehrle-Haller, Bernhard; Bastmeyer, Martin (Frontiers in Bioengineering and Biotechnology, 2022)
Cells mechanical behaviour in physiological environments is mediated by interactions with the extracellular matrix (ECM). In particular, cells can adapt their shape according to the availability of ECM proteins, e.g., fibronectin (FN). Several in vitro experiments usually simulate the ECM by functionalizing the surfaces on which cells grow with FN. However, the mechanisms underlying cell spreading on non-uniformly FN-coated two-dimensional substrates are not clarified yet. In this work, we studied cell spreading on variously functionalized substrates: FN was either uniformly distributed or selectively patterned on flat surfaces, to show that A549, BRL, B16 and NIH 3T3 cell lines are able to sense the overall FN binding sites independently of their spatial arrangement. Instead, only the total amount of available FN influences cells spreading area, which positively correlates to the FN density. Immunocytochemical analysis showed that β1 integrin subunits are mainly responsible for this behaviour, as further confirmed by spreading experiments with β1-deficient cells. In the latter case, indeed, cells areas do not show a dependency on the amount of available FN on the substrates. Therefore, we envision for β1 a predominant role in cells for sensing the number of ECM ligands with respect to other focal adhesion proteins.